Is multiple choice question marks a predictor of the overall students performance? - Mohd Noor, Noriah; Tha, Kyi Kyi; Abdul Razak, Tariq (2011)
This study aims to assess the correlation between the Multiple Choice Questions( MCQs) and the total marks for each Basic Medical Sciences subjects. The Basic Medical Sciences department conducted End of Semester 1 examination session 2009/2010, for year 1 and Year 2 students, Faculty of Pharmacy, International Islamic University Malaysia. The question papers for the various subjects consist of 20-35% MCQs, 50-60% essay and short notes and 10% practical/ OSPE. The MCQs were of the true and false type, and one mark is given for correct answer and one mark will be minus for wrong answer. Mark will not be given if the options is not attempted and the minimum mark for a question with 5 option is zero. The result was analysed by using Microsoft excel. The result of the correlation are as follows; for Physiology,( n= 102, r = 0.82), Anatomy ( n=102, r=0.87), Immunology ( n= 72, r = 0.86), Fundamental of Pharmacology (n=72, r = 0.66) , Peripheral nervous System module ( n=72, r = 0.83), Musculoskeletal system module ( n= 85, r = 0.69). MCQs marks correlated with the total marks, and that, it is a reliable form of assessment technique and is a predictor of the overall students performance if the questions is properly constructed and quality assured.